Hidrogéis de celulose para utilização em curativos - Vuitik, Augusto Araujo (2023)
The treatment of acute and chronic wounds is of great concern for the health systems because it directly impacts the well-being of the patients and the duration of various therapies. In this way, it is crucial to develop technologies that enable shorter and more efficient treatments, which provide more comfort to the patients. Hydrogels are lowcost biocompatible materials that can retain substantial amounts of water and contribute to healing. Silver is largely employed as a biocidal agent from traditional medicine to nowadays treatments, but its production as nanoparticles is up for debate, especially regarding the potentially toxic reagents used in synthesis. This work aims to combine a cellulosic hydrogel with the antimicrobial properties of silver towards an environmentally friendly production. For this purpose, hydrogels of sodium Carboxymethyl Cellulose (CMC) with citric acid as a crosslinker were produced by the cast drying method and then treated with silver particles obtained by chemical reduction of silver nitrate and different reduction agents. The effectiveness of the crosslinking reaction was assessed by infrared spectroscopy using the Attenuated Total Reflectance (ATR) accessory, and the incorporation of silver was assessed by X-Ray Diffraction (XRD), Laser-induced Breakdown Spectroscopy (LIBS) and UV-Vis Spectroscopy. The morphology and composition of the films were also checked by Scanning Electron Microscopy (SEM) with an Energy Dispersive Spectroscopy (EDS) accessory. Microbiological tests were performed through disk diffusion with C. albicans, E. coli and S. aureus. Further functional analysis of the hydrogel evaluated swelling degree and pH. Results indicated the formation of crosslinks in the cast-drying method, and the chemical evaluation pointed to metallic silver. Despite the formation of amorphous particles, they were responsible for the antimicrobial response of the material, confirming the potential for use as a wound dressing.